Professional Identity Development in Nursing Students: Eisner's Evaluation Model - Laleh Hosseini Shahidi; Maryam Vahidi; Behrooz Mahram; Hossein Namdar Areshtanab; Nazila Zarghi (Tabriz University of Medical Sciences, 2014)
Introduction: Professional identity development is one of the main concerns of nursing education. This study aimed to evaluate effective educational components on nursing students' professional identity using Eisner's model of criticism and connoisseurship. Methods: Eisner's Criticism and Connoisseurship Model were used for a qualitative evaluation of the nursing education system. This model includes four steps of descriptive, interpretative, evaluative and thematic evaluation. Data were collected by semi-structured interview and observation. Participants were 15 students and faculty members of Mashhad University of Medical Sciences, Iran, who were selected by purposive sampling. Data were analyzed by Eisner's model. Results: Four major themes included student admission, educational system defects, reality shock, and self-esteem. These themes that emerged from educational evaluation are effective in developing the professional identity of Iranian nursing students. Conclusion: It seems that changing the admission process, presenting the nursing discipline to students as much as possible, creating a more realistic education, making an exclusive body of knowledge, and following successful role models are helpful in students' professional identity development.